EDUCATED UNEMPLOYMENT AND PERSONAL CHARACTER - Susanto, Joko; Siswanto, Yuni (Universitas Negeri Semarang, 2022)
This study identifies the factors causing unemployment of vocational high school graduates due to the mismatch between the mismatch demand and supply of labor. The research uses primary data obtained from questionnaires to several vocational high school graduates accompanied by interviews with several entrepreneurs and labor experts in Yogyakarta Special Region. This study utilizes qualitative analysis obtained through focus group discussions (FGD) and the Delphi method to identify the cause of educated unemployment. The results indicate that the dominant factor in worker’s success is the personal character. The vocational high school graduates have advantages in hard skills and soft skills but they are weak in personal character. If they have not found jobs as they expected, they tend to wait for jobs vacancies. During the waiting process, they are included in the unemployed group. Their choices lead to educated unemployment. Therefore, all the stakeholders should strengthen the youth's character.